Teacher perceptions of parent collaboration in multi-ethnic ECEC settings - Ovati, Tone S. R.; Rydland, Veslemøy; Grøver, Vibeke; Lekhal, Ratib (Frontiers in Education, 2024)
Introduction For teachers working in multi-ethnic early childhood education and care settings, a strong collaboration with parents may be an important mechanism for supporting young children's language development. However, little research has investigated how teachers perceive their communication with parents from diverse backgrounds and what centre-level factors predict the quality of teacher-parent collaboration. Methods This study sought to explore teacher-parent collaboration within early childhood education and care in urban multi-ethnic areas of Norway, using survey data from 266 teachers across 56 centres and 198 classrooms. We examined whether teacher characteristics (education, experience and self-efficacy) and centre linguistic diversity were related to teacher perceived communication with parents regarding ways of supporting children's dual language development and teacher experienced challenges in parent collaboration. Results Results revealed that teachers with higher self-efficacy communicated more with parents and experienced less challenges in collaboration with them. Furthermore, more experienced teachers working in more linguistically diverse centres identified more challenges in parent collaboration, while these characteristics were not related to communication. Teacher education was not associated with communication nor challenges in parent collaboration. Discussion Our results indicate that professional development measures targeted at strengthening teacher self-efficacy might be an important mechanism to promote parent collaboration, particularly in multi-ethnic education settings.